Morpho-physiological response to micronutrient deficiencies and nickel addition of passion fruit plants - Lizcano Toledo, Rodolfo [UNESP]; Melo, Wanderley José de [UNESP]; Prado, Renato de Mello [UNESP]; Olivera Viciedo, Dilier; Peruca de Melo, Gabriel Maurício; de Araújo, Ademir Sérgio Ferreira; Calero Hurtado, Alexander (Taylor & Francis, 2025)
Ultrastructural changes and visual symptoms resulting from nutritional disorders involving boron, manganese, iron, zinc, copper, molybdenum, and nickel depend on the species of the plant, and are unknown in passion fruit plants (Passiflora edulis Sims). A hydroponic experiment evaluated the symptoms of nickel addition and micronutrient deficiency in passion fruit seedlings “BRS Gigante Amarelo” and determined the micronutrient contents in leaf and root tissue, root development, ultrastructural changes (leaf tissue deformations) and dry matter accumulation when visual symptoms were observed. Results showed that the order of manifestation of deficiencies was Fe > Mn > Zn > Cu > Mo > B. Nickel toxicity appeared 40 days after the experiment was started, presenting chlorosis in the new leaves followed by general yellowing and some white parts. Boron omission of resulted in deformations in the leaf limbus and loss of apical dominance, showing deformation of the growth points. Mn omission caused reduction of growth and generalized chlorosis of young leaves with a thick reticulum. Iron omission of resulted in internerval chlorosis with a fine lattice appearance. Omission of zinc and copper resulted in deformation and elongation of the leaves, reducing height and root development. Molybdenum omission caused chlorosis in the older leaves, which was observed to spread over time. Iron was the nutrient that most reflected symptoms of deficiency by the formation of root hairs. The findings of this research suggest that the knowledgement of plant micronutrients status permits an understanding of the physiological responses of passion fruit plants to crop fertilization.
Keywords: Chloroplast; micronutrient deficiency; nickel toxicity; root hairs; thylakoid